ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KECENDERUNGAN PENERIMAAN OPINI AUDIT GOING CONCERN - Hanif Adibi, 08.05.52.0171; Kartika, Andi (Students Journal of Accounting and Banking, 2012)
This study aims to determine and examine the effect of audit quality, financial condition, leverage, firm growth and size of the companys revenues going concern audit opinion.This study uses 30 manufacturing companies listed on the Indonesia Stock Exchange in 2007-2010. Samples obtained by purposive sampling. Type of data used was secondary data of every manufacturing company listed on the Indonesia Stock Exchange during the four years the year 2007-2010. The research data were analyzed with logistic regression analysis.The results showed that (1) The quality of the audit did not affect the going concern audit opinion. (2) The financial condition did not affect the going concern audit opinion. (3) Leverage did not affect the going -concern audit opinion. (4) Growth did not affect the going-concern audit opinion. (5) The size of the company did not affect the going concern audit opinion.Keywords: quality audit, financial condition, leverage, growth, firm size and revenues going concern audit opinion